The Android mobile application to assess mothers' knowledge, attitudes, and behaviors related to the prevention of stunting in children under two years old - Gustina, Mely; Yorita, Epti; Sari, Aplina Kartika; Utama, Feranita; Haryono, Haryono (Program Studi Ilmu Keperawatan-fakultas Ilmu Kesehatan Universitas Malahayati, 2025)
Background: Stunting remains a major public health problem in Indonesia, with prevalence rates that exceed the World Health Organization threshold. In Bengkulu Province, particularly in the Kampung Melayu Subdistrict, stunting is exacerbated by limited access to health services, low maternal knowledge, unfavorable attitudes, and inadequate sanitation-related preventive behaviors. These factors contribute to recurrent infections and impaired nutrient absorption in children under two years old. The use of digital-based educational media is considered a promising strategy to improve health literacy and promote positive behavioral change among mothers. Purpose: To evaluate the effectiveness of the Android mobile application to assess mothers' knowledge, attitudes, and behaviors related to the prevention of stunting in children under two years old in the Kampung Melayu Subdistrict, Bengkulu City. Method: A quasi-experimental design with a control group. A total of 80 participants were selected using purposive sampling and divided into an intervention group (n = 40) and a control group (n = 40). The intervention group received health education through the SESAMA Android application, while the control group received conventional health promotion. Data were analyzed using Wilcoxon test, Paired T-test, Mann–Whitney test, ANCOVA, and MANCOVA. Results: The intervention group showed a significant improvement in knowledge, attitudes, and preventive behaviors related to stunting (p = 0.000). Mean knowledge scores increased from 5.60 to 8.23, attitude scores from 35.58 to 39.50, and behavior scores from 11.18 to 15.73. In contrast, the control group showed a significant improvement only in knowledge (p = 0.041), with no significant changes in attitudes (p = 0.172) or behaviors (p = 0.083). MANCOVA analysis confirmed that the SESAMA application had a significant effect on knowledge (p = 0.000; R² = 0.298), attitudes (p = 0.000; R² = 0.166), and behaviors (p = 0.000; R² = 0.584), with the strongest effect observed on preventive behavior. Conclusion: The SESAMA Android-based educational application is effective in improving maternal knowledge, attitudes, and behaviors related to stunting prevention and demonstrates greater effectiveness compared to conventional health promotion methods. The SESAMA model has strong potential to support digital health education strategies and may be considered for broader implementation in stunting prevention programs.